A market-oriented innovative quality framework for the investigation of competitive entry opportunities into new seafood markets for producers. (1st January 2013) - Yusuf, Muhammad; Trondsen, Torbjørn
This paper develops a theoretical foundation for investigating effective market-oriented strategies to enable entry into new seafood markets by means of innovation and product quality advantages. The introduction of new products to the market is associated with several factors primarily including: (1) market openness and demand for new product attributes; (2) business orientation and strategies in marketing management throughout the value chain; (3) the value chain structure; (4) regulation of the value chain; (5) balances and trends in supply and demand. The relationship between these factors is understood by combining theories of Barney's VRIO concept, the five stages of Rogers' innovation-decision process model and Porter's five forces of competition position model, summarised in a market-oriented innovative quality (MOIQ) framework.